2020
DOI: 10.3329/pa.v31i1.48311
|View full text |Cite
|
Sign up to set email alerts
|

Economic assessment of lemon-based agroforestry systems established in Madhupur Sal forest area of Bangladesh

Abstract: The study was carried out to determine the economic assessment of lemon-based agroforestry systems established in the Madhupur Sal forest during the period from May 2017 to September 2018. The study selected five lemon-based agroforestry systems viz. Lemon-Mango-Pineapple-Papaya-Ginger, Lemon-Pineapple-Papaya-Banana-Aroid, Lemon-Pineapple-Papaya-Ginger, Lemon-Mango-Turmeric-Red amaranth and Lemon-Litchi-Papaya-Banana along with three replications having 0.13 ha area for each sample plot. The control plots (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…The climatic condition and soil type of this area found frequently favours for growth of lemon orchards and their productivity. Our result is more or less comparable with the published work of (Hasan et al, 2020), they worked on benefit cost ratio of lemon based agro-forestry systems at Madhupur, India and proved lemon-based agro-forestry systems are more profitable than sole cropping cultivation. Dubey et al (2023), proved optimized foliar application with significant effect of micronutrients on yield attributes and economic feasibility of lemon orchards.…”
Section: Benefit-cost Ratio Of Lemon Orchards and Fruits From Five Ta...supporting
confidence: 90%
“…The climatic condition and soil type of this area found frequently favours for growth of lemon orchards and their productivity. Our result is more or less comparable with the published work of (Hasan et al, 2020), they worked on benefit cost ratio of lemon based agro-forestry systems at Madhupur, India and proved lemon-based agro-forestry systems are more profitable than sole cropping cultivation. Dubey et al (2023), proved optimized foliar application with significant effect of micronutrients on yield attributes and economic feasibility of lemon orchards.…”
Section: Benefit-cost Ratio Of Lemon Orchards and Fruits From Five Ta...supporting
confidence: 90%
“…Further, 29%of people opined that 30-35kg firewood is collected daily to earn income, followed by 17% responding that 40-45kg fuelwood for commercial sale and 8% of them saying that 15-20kg is being collected for Forest Department staff. Similar research findings revealed that an average 11-15kg of fuelwood is collected daily for household consumption in Modhupur National Park (MNP) (Hossain et al, 2015;Hasan et al, 2020).…”
Section: Daily Fuelwood Collectionsupporting
confidence: 62%
“…Previous studies have reported that the agricultural activities cash crops and corn producing for Modhupur National Park (MNP) are 21% and 62%, respectively (Hossain et al, 2015;Hasan et al, 2020). Forest fire is an utmost cause for degradation and depletion of forest resources (Hossain et al, 2015).…”
Section: Agricultural Activitiesmentioning
confidence: 99%
“…Net return justifies the profitability of the MAFS which is derived from deduction of total cost with gross return. Then the following formula was used to estimate BCR [35]:…”
Section: Economic Performancementioning
confidence: 99%